The Influence of Islamic Religious Education on the Formation of Religious Moderation Attitudes of Students - Gafarurrozi, Muhammad; Suyadi; Arifi, Ahmad (LPPM Universitas Ibn Khaldun, Bogor, 2026)
This study aims to analyze the influence of Islamic Religious Education (PAI) learning on the attitude of religious moderation of students in salafi-affiliated Islamic boarding schools. This issue is important considering the strong assumption that salafi theological orientation tends to correlate with exclusive religious attitudes. This study uses a quantitative approach with a survey design of 261 students. Data were analyzed using simple linear regression to test the relationship between PAI learning as an independent variable and religious moderation attitudes as a dependent variable. The results of the analysis showed that PAI learning had a positive and significant effect on the attitude of religious moderation of students with a sig value of 0.000 < 0.05 and a t-count value of 16,561 > t-table of 1.97. These findings indicate that the improvement of the quality of PAI learning is consistently followed by an increase in the attitude of religious moderation of students. The results of this study confirm that religious moderation does not contradict Salafi manhaj, but can grow contextually through a pedagogical process that emphasizes tafaqquh fi al-din, adab al-ikhtilaf, and the formation of social morals. This research empirically contributes to enriching the discourse of Islamic education by showing that PAI learning acts as a mediation mechanism between theological firmness and social openness in the Salafi Islamic boarding school environment. These findings have important implications for the development of a contextual religious moderation education model rooted in Islamic scientific traditions.